FUNCTIONAL PROPERTIES OF COMBINED WEAR RESISTANT Ti-BASED COATINGS ON HIGH SPEED STEEL - M. A. Andreyev; T. A. Kuznetsova; L. V. Markova (Наука и техника)
Functional properties of wear resistant combined coatings based on Ti are investigated in the paper. The coatings have been obtained with the help of combined technology that used electro arc evaporation and ionic nitriding methods. Wear resistance of the combined coating is five-fold higher than a standard TiN coating. The high-wear resistance is attributed to a secondary structure, which appears in the friction zone on the surface of the combined coating.